Pesticide residues in water samples of some paddy fields in Narayangonj (Chittagong University Journal of Biological Sciences, 2013)
DOI: http://dx.doi.org/10.3329/cujbs.v5i1.13381 The Chittagong Univ. J. B. Sci.,Vol. 5(1 &2):155-157, 2010